PENGARUH SOSIAL MEDIA MARKETING, E-SERVICE QUALITY, DAN REVIEW CONTENT TERHADAP MINAT BELI KONSUMEN BOX OUTLET SINGARAJA - KUSUMA, EKA; DEWI, KOMANG AYU INTAN (GANEC SWARA, 2024)
This study aims to examine the influence of Social Media Marketing, E-Service Quality, and Review Content on consumer buying interest in  Singaraja Box Outlet  Stores. The population in this study includes all Singaraja Box Outlet  Store consumers from various walks of life, both men and women. The sample used in this study was 85 consumers selected through a questionnaire technique distributed using Google Form. This study used a quantitative approach and the data was analyzed by multiple linear regression method using IBM SPSS Statistics 25 application. The results showed that Social Media Marketing, E-Service Quality and Review Content proved to have a positive and significant influence on consumer buying interest in Singaraja Box Outlet  Stores